18F-FDG PET/CT in patients with adult-onset Still's disease. Issue 12 (December 2015) - Dong, Meng-Jie; Wang, Cai-qin; Zhao, Kui; Wang, Guo-Lin; Sun, Mei-Ling; Liu, Zhen-Feng; Xu, Liqin
Abstract 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (18 F-FDG PET/CT) has become useful for the detection and diagnosis of inflammatory conditions, including rheumatic diseases, immunoglobulin (Ig) G4-related disease and giant cell arteritis. However, few articles based on small sample sizes (n  = 7) diagnosed as adult-onset Still's disease (AOSD) have been published. The study aim was to observe the reliable characteristics and usefulness of18 F-FDG PET/CT for the evaluation of consecutive patients with AOSD. Eligible patients were selected from among those who had undergone18 F-FDG PET/CT between May 2007 and June 2014. Twenty-six consecutive AOSD patients were recruited retrospectively according to criteria set by Yamaguchi et al. All patients underwent evaluation by18 F-FDG PET/CT. The characteristics and usefulness of18 F-FDG PET/CT for evaluation of consecutive patients with AOSD were evaluated. All 26 patients had18 F-FDG-avid lesion(s) related to their particular disease. Diffuse and homogeneous accumulation of18 F-FDG was seen in the bone marrow (26/26; 100 %; maximum standardized uptake (SUVmax ), 2.10–6.73) and spleen (25/26; 96.15 %). The SUVmax of affected lymph nodes was 1.3–9.53 (mean ± SD, 4.12 ± 2.24). The SUVmax and size factors (maximum diameter and areas) of affected lymph nodes were significantly different (P  = 0.033 andP  = 0.012, respectively).18 F-FDG PET/CT showed the general distribution of18 F-FDG accumulation. This factor helped to exclude malignant disease and aided the diagnosis of AOSD (42.3 %) in 11 cases when combined with clinical features and aided decisions regarding appropriate biopsy sites, such as the lymph nodes (n  = 9) and bone marrow (n  = 13).18 F-FDG PET/CT is a unique imaging method for the assessment of metabolic activity throughout the body in subjects with AOSD. Characteristics or patterns of AOSD observed on18 F-FDG PET/CT can be used for the indication and diagnosis or to guide the clinical management of ASOD.